(untitled) (World Bulletin of Social Sciences, 2024)
This study examines the development of speaking fluency in English as a foreign language (EFL) contexts. Speaking fluency is a crucial aspect of language proficiency, yet it is often challenging for EFL learners to master. The research aims to analyze the factors influencing speaking fluency development, such as language input, practice opportunities, and learner motivation. The study employs both quantitative and qualitative methods to explore the progress of a group of EFL learners over a specific period. Findings suggest that targeted practice, exposure to authentic language input, and learner motivation are key factors in enhancing speaking fluency in EFL contexts.